Exploring Ketamine’s Expanding Roles Beyond Anesthesia, Including PTSD, Chronic Pain, and Depression Treatment - Jawad Hameed, Roheena Wadud (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: Ketamine, traditionally known for its anesthetic properties, is now being explored for its rapid-acting therapeutic effects in various psychiatric and pain-related disorders. Its emerging role in managing treatment-resistant depression (TRD), chronic pain, and post-traumatic stress disorder (PTSD) is supported by recent clinical evidence. Objective: To evaluate the effectiveness of ketamine in the treatment of chronic pain, TRD, and PTSD among patients in a tertiary care setting. Materials and Method: This retrospective observational study was conducted at Anesthesia Department, Lady Reading Hospital-MTI Peshawar, Pakistan, from January, 2023 to June, 2023. Based on the predetermined inclusion and exclusion criteria, 70 records for patients receiving ketamine treatment were assessed. Clinical outcomes were assessed using standardized rating scales for pain, depression, and PTSD. Results: Substantial healing occurred for each condition, and symptom severity was significantly reduced following ketamine treatment. Overall, 78.5% of patients had positive responses with no adverse effects. Conclusion: Ketamine represents a viable and fast-acting alternative treatment for patients with refractory psychiatric conditions and pain. Keywords: Ketamine, depression, PTSD, chronic pain, treatment-resistant, rapid-acting therapy, NMDA antagonist.